The Influence of Service Quality and Brand Trust on Brand Image and Its Implications on Panin Bank Customer Loyalty in the Use of Mobile Banking - Ferdiansyah, Ferdiansyah; Sudarso, Aden Prawiro (Economic and Business Horizon, 2024)
This study was conducted to identify PANIN customer loyalty in mobile banking by using service quality, brand trust, and brand image. The sampling technique used is purposive sampling with the criteria (1) customers have a PANIN mobile application; (2) over 17 years old; (3) have used the app at least once. Data were obtained from questionnaires using Google Forms. Received a sample of 340 respondents, the test is carried out by SEM analysis using AMOS 24 software. The analysis using AMOS 24 shows that: (1). Service quality affects brand image. (2). Brand trust affects brand image (3). Service quality affects customer loyalty (4). Brand trust affects customer loyalty. (5) brand image affects customer loyalty. (6) Service quality mediated by brand image affects customer loyalty. (7) Brand trust mediated by brand image affects customer loyalty.